Marine Hydroquinone Zonarol Prevents Inflammation and Apoptosis in Dextran Sulfate Sodium-Induced Mice Ulcerative Colitis - Yamada, Sohsuke; Koyama, Tomoyuki; Noguchi, Hirotsugu; Ueda, Yuki; Kitsuyama, Ryo; Shimizu, Hiroya; Tanimoto, Akihide; Wang, Ke-Yong; Nawata, Aya; Nakayama, Toshiyuki; Sasaguri, Yasuyuki; Satoh, Takumi (PLOS ONE, 2014)
Background and Aim We previously identified an anti-inflammatory compound, zonarol, a hydroquinone isolated from the brown algae Dictyopteris undulata as a marine natural product. To ascertain the in vivo functions of zonarol, we examined the pharmacological effects of zonarol administration on dextran sulfate sodium (DSS)-induced inflammation in a mouse model of ulcerative colitis (UC). Our goal is to establish a safe and effective cure for inflammatory bowel disease (IBD) using zonarol. Methods and Results We subjected Slc:ICR mice to the administration of 2% DSS in drinking water for 14 days. At the same time, 5-aminosalicylic acid (5-ASA) at a dose of 50 mg/kg (positive control) and zonarol at doses of 10 and 20 mg/kg, were given orally once a day. DSS-treated animals developed symptoms similar to those of human UC, such as severe bloody diarrhea, which were evaluated by the disease activity index (DAI). Treatment with 20 mg/kg of zonarol, as well as 5-ASA, significantly suppressed the DAI score, and also led to a reduced colonic ulcer length and/or mucosal inflammatory infiltration by various immune cells, especially macrophages. Zonarol treatment significantly reduced the expression of pro-inflammatory signaling molecules, and prevented the apoptosis of intestinal epithelial cells. Finally, zonarol protected against in vitro lipopolysaccharide (LPS)-induced activation in the RAW264.7 mouse macrophage cell line. Conclusions This is the first report that a marine bioproduct protects against experimental UC via the inhibition of both inflammation and apoptosis, very similar to the standard-of-care sulfasalazine, a well-known prodrug that releases 5-ASA. We believe that the oral administration of zonarol might offer a better treatment for human IBDs than 5-ASA, or may be useful as an alternative/additive therapeutic strategy against UC, without any evidence of side effects.